A Novel Regulatory Role for RPS4Y1 in Inflammatory and Fibrotic Processes - Reddy, Karosham D.; Rathnayake, Senani N. H.; Idrees, Sobia; Boedijono, Fia; Xenaki, Dikaia; Padula, Matthew P.; Berge, Maarten van den; Faiz, Alen; Oliver, Brian G. G. (International journal of molecular sciences, 2025)
Asthma is a chronic inflammatory respiratory disease well-known to demonstrate sexual dimorphism in incidence and severity, although the mechanisms causing these differences remain incompletely understood. RPS4X and RPS4Y1 are X and Y-chromosome-linked genes coding ribosomal subunits previously associated with inflammation, airway remodelling and asthma medication efficacy. Particularly, RPS4Y1 has been under-investigated within the context of disease, with little examination of molecular mechanisms and pathways regulated by this gene. The ribosome, a vital cellular machinery, facilitates the translation of mRNA into peptides and then proteins. Imbalance or dysfunction in ribosomal components may lead to malfunctioning proteins. Using CRISPR-Cas9 knockout cellular models for RPS4Y1 and RPS4X, we characterised the function of RPS4Y1 in the context of the asthma-relevant processes, inflammation and fibrosis. No viable RPS4X knockouts could be generated. We highlight novel molecular mechanisms such as specific translation of IL6 and tenascin-C mRNA by RPS4Y1 containing ribosomes. Furthermore, an RPS4Y1-centric gene signature correlates with clinical lung function measurements, specifically in adult male asthma patients. These findings inform the current understanding of sex differences in asthma, as females do not produce the RPS4Y1 protein. Therefore, the pathologically relevant functions of RPS4Y1 may contribute to the complex sexually dimorphic pattern of asthma susceptibility and progression.